2017
DOI: 10.1038/pr.2017.187
|View full text |Cite
|
Sign up to set email alerts
|

The triglycerides and glucose index is associated with cardiovascular risk factors in normal-weight children and adolescents

Abstract: BackgroundGiven the usefulness of the product of triglycerides and glucose (TyG) to recognize individuals at high risk for developing cardiovascular events, the aim of this study was to determine whether the TyG index is associated with the presence of cardiovascular risk factors in apparently healthy normal-weight children and adolescents.MethodsApparently healthy children and adolescents with normal weight, aged 6-15 years, were enrolled in a population-based cross-sectional study. The children were allocate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…In our study, we found similar cut-off values for boys and girls (8.38 vs 8.27). Moreover, similar cut-off values have been reached in a limited number of studies conducted in different countries (7.8-8.65) [15][16][17][18][19][20][21][22][23][24] . Moon et al 20 showed that 12-19 years old 8037 adolescents the cut-off values for the Ty-G index ranged from 8.15-8.65 in Mexican American, Non-Hispanic White, Korean, and Non-Hispanic Black adolescents.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In our study, we found similar cut-off values for boys and girls (8.38 vs 8.27). Moreover, similar cut-off values have been reached in a limited number of studies conducted in different countries (7.8-8.65) [15][16][17][18][19][20][21][22][23][24] . Moon et al 20 showed that 12-19 years old 8037 adolescents the cut-off values for the Ty-G index ranged from 8.15-8.65 in Mexican American, Non-Hispanic White, Korean, and Non-Hispanic Black adolescents.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, emerged studies have shown that the Ty-G index can accept as a marker of IR, that is correlated with both the euglycemic clamp test and the HOMA-IR levels [7][8][9] There is a lot of study in adults investigating the Ty-G index [15][16][17][18] . However, a limited study in pediatric age group [19][20][21][22][23][24] . Moreover, to the best of our knowledge, there is no study on Turkish children.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the current study, the accumulation of cardiometabolic risk factors in children with high TyG index was higher in relation to the others. Simental-Mendía et al (39) , in a study with children and adolescents aged 6-15 years, observed that those distributed in the highest quintile of the TyG index had higher prevalence of cardiometabolic risk in relation to the others, suggesting a direct association between cardiovascular risk and the increased TyG index. Some positive points of the current study should be considered.…”
Section: Discussionmentioning
confidence: 97%
“…The TyG index has been shown to be clinically useful in the identification of the metabolic syndrome [ 97 , 98 ]. Increased TyG index has been associated with the presence of risk factors for cardiovascular disease in healthy children and adolescents with a normal body weight [ 99 ]. Lee et al, who tested the role of the TyG index in identifying MONW subjects, proposed a TyG cut-off value for MONW ≥ 8.82 for men and ≥8.73 for women [ 90 ].…”
Section: Biochemical Markers In Monwmentioning
confidence: 99%